2009
DOI: 10.1111/j.1745-4573.2009.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Realimentation of Cull Beef Cows. Ii. Meat Quality of Muscles From the Chuck, Loin and Round in Response to Diet and Enhancement

Abstract: From an experiment in which 60 beef cull cows were assigned to one of three feeding treatments, forage fed, high concentrate or high concentrate plus ractopamine, 10 muscles were removed from both sides of the carcass. Muscles from one side of the carcass were enhanced with a solution to target 0.3% salt and 0.3% phosphate in the final product. Minimal to no differences were observed in color, pH, sensory characteristics or shear force as a result of dietary treatment. Enhancement resulted in muscles with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(39 reference statements)
3
9
1
Order By: Relevance
“…As previously reported in young animals, enhancement improved beef flavor; however, there was also a heightened detection of off flavor in enhanced muscles. In the current study, the beef flavor intensity was less in enhanced cow compared with nonenhanced cow in all 3 subprimals, which contradicts the findings of Holmer et al (2009). Wicklund et al (2005) speculated that enhancement solution ingredients, particularly salt, were capable of masking other flavors.…”
Section: Sensory Analyses Of Palatabilitycontrasting
confidence: 98%
See 2 more Smart Citations
“…As previously reported in young animals, enhancement improved beef flavor; however, there was also a heightened detection of off flavor in enhanced muscles. In the current study, the beef flavor intensity was less in enhanced cow compared with nonenhanced cow in all 3 subprimals, which contradicts the findings of Holmer et al (2009). Wicklund et al (2005) speculated that enhancement solution ingredients, particularly salt, were capable of masking other flavors.…”
Section: Sensory Analyses Of Palatabilitycontrasting
confidence: 98%
“…Nonenhanced cow steaks were intermediate, whereas enhanced cow steaks were the least. These results are consistent with Holmer et al (2009) that reported enhanced muscles from beef cull cows were visually darker and had less L*, a*, and b* values than nonenhanced muscles. Although enhanced cow steaks in the current study had the darkest muscle color, they had less surface discoloration than nonenhanced cow or Select steaks, which did not differ.…”
Section: Color Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, RH would be expected to have less of an effect on tenderness than ZH. In agreement with our results, Holmer, Homm, Berger, Stetzer, et al (2009) reported that feeding RH to cows had no adverse affects on WBSF values of LM steaks. Additionally, RH supplementation has been reported to slightly increase WBSF values in steers and heifers, but the impact on consumer Table 1 Least squares means for Warner Bratzler shear force of psoas major, infraspinatus, non-enhanced longissimus, and calcium lactate-enhanced longissimus steaks and sensory traits of psoas major and calcium lactate-enhanced longissimus steaks from mature cows fed a high-energy ration for 74 d with or without β-adrenergic agonist supplementation.…”
Section: Non-enhanced Longissimus Warner Bratzler Shear Force and Sensupporting
confidence: 95%
“…For PM WBSF, steaks from the RH + ZH treatment had a lower numerical value than those from the RH treatment (2.8 versus 3.2 kg; P = 0.12). Holmer, Homm, Berger, Stetzer, et al (2009) reported that PM steaks from cows supplemented with RH tended (P = 0.10) to have higher WBSF values. No other published literature has looked at the influence of β-AA in cull cow feeding systems on PM tenderness.…”
Section: Psoas Major and Infraspinatus Warner Bratzler Shear Force Anmentioning
confidence: 95%